Public participation in managing waste through channels of communication: the role of environmental education and awareness programmes in Malaysian public universities - Hashim, Khairusy Syakirin Has-Yun; Abdullah @ Sudin, Handzalah; Mohammed, Abdul Hakim (USM, 2012)
Public participation is part of the National Strategic Plan for Solid Waste Management which has been outlined by the National Solid Waste Management Department, Ministry of Housing and Local Government. Encouraging public participation has been considered as one of the strategies to solve the waste problems in Malaysia. There are two factors which can influence public to participate in managing waste, i.e. environmental education and awareness programmes. Thus, the aims of this paper are to further investigate on (1) how public could participate and contribute in a decision making process to manage waste, by focusing on universities’ students, (2) the role of environmental education to the development of public participation and (3) the role and method used to develop the awareness programmes towards developing the public participation. Hence, the methodology used in this research is by using questionnaires, distributed among students at three public universities. The findings of this research will be used to develop the Waste Minimization Awareness Model.